The Role of Noninvasive Imaging for Detection High Risk Patients with Subclinical Atherosclerosis - Krasimira Hristova (Archives of Clinical Hypertension - Peertechz Publications, 2016)
Non-invasive imaging is widely used to assess vascular dysfunction, including measurement of flow-mediated vasodilatation of the brachial artery (FMD), pulse wave velocity (PWV), the augmentation index (AI), and central blood pressure. Endothelial dysfunction, a main contributor of atherosclerosis is possible diagnostic tool by FMD. An arterial stiffness, assessing by the PWV and/or arterial dispensability and beta stiffness index have been associated with cardiovascular risk. Ultrasound-based methods are used to assess elastic properties of the arterial walls in studies of arterial stiffness and atherosclerosis. In asymptomatic individuals is essential in order to detect, predict and prevent cardiovascular diseases first be estimated based on the global assessment of risk factors? Nowadays is recommended in daily routine screening for coronary artery disease in asymptomatic individuals with intermediate (10-20% 10-year risk of coronary artery disease) or high risk (>20% 10-year risk of coronary artery disease) to provide a  urther screening.